Methyl hydroperoxide (CH3OOH) in urban, suburban and rural atmosphere: ambient concentration, budget, and contribution to the atmospheric oxidizing capacity - Y. Zhao; W. Hua; Z. M. Chen; S. Z. He; X. Zhang (Atmospheric Chemistry and Physics, 2012)
Methyl hydroperoxide (MHP), one of the most important organic peroxides in the atmosphere, contributes to the tropospheric oxidizing capacity either directly as an oxidant or indirectly as a free radical precursor. In this study we report measurements of MHP from seven field campaigns at urban, suburban and rural sites in China in winter 2007 and summer 2006/2007/2008. MHP was usually present in the order of several hundreds of pptv level, but the average mixing ratios have shown a wide range depending on the season and measuring site. Primary sources and sinks of MHP are investigated to understand the impact of meteorological and chemical parameters on the atmospheric MHP budget. The MHP/(MHP+H2O2) ratio is also presented here to examine different sensitivities of MHP and H2O2 to certain atmospheric processes. The diurnal cycle of MHP/(MHP+H2O2), which is out of phase with that of both H2O2 and MHP, could imply that MHP production is more sensitive to the ambient NO concentration, while H2O2 is more strongly influenced by the wet deposition and the subsequent aqueous chemistry. It is interesting to note that our observation at urban Beijing site in winter 2007 provides evidence for the occasional transport of MHP-containing air masses from the marine boundary layer to the continent. Furthermore, the contribution of MHP as an atmospheric oxidant to the oxidizing capacity of an air parcel is assessed based on the "Counter Species" concept.